Development and Evaluation of a Pilot Short-Term Mental Health Curriculum with Longitudinal Evaluation for Minority Youth - Granberry, Robin; Mathesh, Vivek; Ford, Lauren; Thompson, Wesley; Loria, Hilda; Pak, Thomas K. (International Journal of Medical Students, 2025)
Background: Minority youth are susceptible to mental health issues in the United States. Early intervention with a mental health curriculum is valuable in building resilience and wellness. Our study’s purpose was to design, implement and evaluate a mental health curriculum (Mental Health Matters) for minority youth in a local community center. Methods: We conducted a needs assessment of mental health topics important for minority youth. Pre-and post-lesson surveys were administered at each session to measure students’ knowledge and understanding of lesson objectives. We analyzed paired data using a Wilcoxon signed-rank test. Results: The needs assessment identified a need for educating youth about emotional insight and regulation and interpersonal communication. From the needs assessment, we worked with a local community organization to design a short-term longitudinal mental health curriculum. With the same local community organization, we implemented the curriculum to an after-school program for minority youth. The pre- and post-survey showed the students gained a significant increase of perceived confidence: fundamentals of mental health (p=0.008); stress response, box breathing, and perceiving stress (p=0.046); coping skills (p=0.025); communication styles/conflict resolution strategies (p=0.031). Qualitative feedback from students and administrators indicated strengths of the curriculum included its adaptability and applicability to students’ lives. Conclusion: Overall, we successfully developed a pilot mental health curriculum based on a community needs assessment for minority youth.